PENGGUNAAN INTERNET DAN KETERAMPILAN DIGITAL: PEMBELAJARAN DARING DI KALANGAN DOSEN DAN MAHASISWA PADA MASA PANDEMI COVID-19 - Diah Febrina; Umar Halim; Rosmalia Ahmad (LPPM Universitas Cipta Mandiri, 2024)
At the end of 2019, the world was shocked by the emergence of the COVID-19 virus which is thought to have originated from the city of Wuhan, China. The COVID-19 pandemic has affected various fields, including education. Indonesia, through the Ministry of Education and Culture, has taken steps to prevent the spread of the corona virus disease (COVID-19) by issuing a circular regarding online learning and working from home. This study aims to determine the level of internet use as a medium for online learning between lecturers and students, and the differences in digital skill levels between lecturers and students. The method used is quantitative, involving 31 lecturers and 91 students. The results of the study showed that lecturers and students use the internet to surf social media, surf through search engines such as Google or Yahoo, and watch using YouTube, Netflix, and other applications. Lecturers and students use laptops or notebooks and smartphones and utilize the Zoom and WhatsApp applications for online learning. Other results reveal differences in digital skills between lecturers and students